2010
DOI: 10.1152/jn.00503.2009
|View full text |Cite
|
Sign up to set email alerts
|

Coding of Stimuli by Ampullary Afferents inGnathonemus petersii

Abstract: Weakly electric fish use electroreception for both active and passive electrolocation and for electrocommunication. While both active and passive electrolocation systems are prominent in weakly electric Mormyriform fishes, knowledge of their passive electrolocation ability is still scarce. To better estimate the contribution of passive electric sensing to the orientation toward electric stimuli in weakly electric fishes, we investigated frequency tuning applying classical input-output characterization and stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 55 publications
2
29
0
Order By: Relevance
“…Therefore, RR coherence is used to estimate an upper bound of mutual information rate. 24,45 Closeness of the SR coherence to the square root of the RR coherence indicates that a linear encoding scenario is optimal, whereas large departures indicate that a linear encoding model is not appropriate.…”
Section: B Data Analysesmentioning
confidence: 99%
“…Therefore, RR coherence is used to estimate an upper bound of mutual information rate. 24,45 Closeness of the SR coherence to the square root of the RR coherence indicates that a linear encoding scenario is optimal, whereas large departures indicate that a linear encoding model is not appropriate.…”
Section: B Data Analysesmentioning
confidence: 99%
“…Neuronally, sensory adaptation is characterized by a decrease in responsiveness over the duration of a constant-amplitude stimulus (Adrian 1928). This phenomenon, generally described as spike frequency adaptation, has been found in numerous studies in both vertebrate and invertebrate sensory systems, e.g., in the visual (e.g., Laughlin 1989;Peron and Gabbiani 2009), olfactory (e.g., Demmer and Kloppenburg 2009), electrosensory (e.g., Nelson et al 1997;Benda et al 2005;Engelmann et al 2010), and auditory system (e.g., Westermann and Smith 1984;Epping 1990; Givois and Pollack 2000;Ronacher and Hennig 2004). Adaptive responses can result from different mechanisms, including the transduction process of receptor neurons (Hudspeth et al 2000;Gollisch and Herz 2004;Albert et al 2007), synaptic depression (Abbott et al 1997;Chance et al 1998), inhibitory inputs (Finlayson and Adam 1997;Ingham and McAlpine 2004), or ionic currents modulating spike generation (e.g., Benda and Herz 2003;Benda and Tabak 2014;Benda et al 2010).…”
Section: Introductionmentioning
confidence: 81%
“…As recently shown, the ampullary receptors of bony fish are evolutionary derived from lateral line receptors (Modrell et al 2011). Various reports have demonstrated that the responses to sustained DC step stimuli of afferent nerve fibres innervating ampullary (Engelmann et al 2010) and tuberous receptors (Xu et al 1996;Benda et al 2005) are adapting. Different models have been applied to in vivo data, including exponential, logarithmic, and power law models, to describe the time course of adaptation of electrosensory afferents (e.g., Benda et al 2010;Clarke et al 2013;Engelmann et al 2010;Xu et al 1996).…”
Section: Time Course and Mechanisms Of Adaptationmentioning
confidence: 98%
See 2 more Smart Citations